Hadrian, a Numismatic Lapse, and… Janus: - Kluczek, Agata A. (Studia Ceranea, 2023)
The image of the “founder”, who marks the boundaries of the city with a plough drawn by a pair of animals was one of the obvious themes placed on the reverses of colonial coins. Such a symbolic foundation scene (aratrum motif) was also one of the leading themes on coins from the colonial mint in Parium in the east of the Roman Empire. During the reign of Hadrian (AD 117–138), this mint issued coins (RPC 3, nos 1539 and 1540), which, apart from the aratrum motif, have an unobvious legend on their reverses, especially in its connection with the obverse inscription on these coins.